Molecular dynamics simulations of ternary lipid bilayers containing plant sterol and glucosylceramide. (March 2017) - Emami, Shiva; Azadmard-Damirchi, Sodeif; Peighambardoust, Seyed Hadi; Hesari, Javad; Valizadeh, Hadi; Faller, Roland
Highlights: Differential condensing and ordering effects of sitosterol and cholesterol. Cholesterol slightly more efficient than sitosterol in packing the membrane. Clusters of GlcCer/sterol form at ratio of GlcCer larger than 15.5%. Abstract: An atomic-level molecular dynamics simulation was carried out to study the effects of a plant sterol (sitosterol) and glucosylceramide (GlcCer) on a 1, 2-dilinoleoylposphocholine (DLiPC) membrane. Initially, a membrane containing 50 mol% sitosterol was compared with that containing the same ratio of cholesterol. These simulations showed differential condensing and ordering effects of sitosterol and cholesterol, with cholesterol being slightly more efficient than sitosterol in packing the membrane more tightly to a liquid ordered phase. By incorporation of 9.3% GlcCer on DLiPC/sterol membrane no notable change was observed in terms of area per lipid, bilayer thickness, order parameter and lateral diffusion. Some clusters of GlcCer/sterol were observed at higher ratio of GlcCer (15.5%), supporting the existence of GlcCer/sitosterol-enriched Lo -domains on the nanometer scale in the plant lipid mixture.